2011
DOI: 10.1177/03946320110240s402
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Disease and Asthma

Abstract: The nose plays a primary role within the airways, working as "a filter and air-conditioner", together with other important fnnctions. Thus, it is not surprising that nasal diseases are associated with several other comorbidities, including both upper and lower airways, such as bronchial hyperresponsiveness (BHR) and asthma. Several studies have investigated the relationship existing between the upper and the lower airways and new insights are rising. Nevertheless, some uncertainties still remain, mainly becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…According to some studies (8), asthma is more common in patients with moderate-to-severe persistent rhinitis; according to others, there is no correlation between ARIA categories of rhinitis and prevalence of asthma (9). Rhinitis is a significant and independent risk factor for asthma onset, as it often precedes bronchial hyperreactivity (1). AR has also been linked to "small airway disease", defined as a reduction in forced expiratory flow (PEP) at 25%-75% of the pulmonary volume and a normal spirometry, which is suggested to be an early marker of bronchial involvement in patients with rhinitis who perceive only nasal symptoms (10).…”
Section: Epidemiologic Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies (8), asthma is more common in patients with moderate-to-severe persistent rhinitis; according to others, there is no correlation between ARIA categories of rhinitis and prevalence of asthma (9). Rhinitis is a significant and independent risk factor for asthma onset, as it often precedes bronchial hyperreactivity (1). AR has also been linked to "small airway disease", defined as a reduction in forced expiratory flow (PEP) at 25%-75% of the pulmonary volume and a normal spirometry, which is suggested to be an early marker of bronchial involvement in patients with rhinitis who perceive only nasal symptoms (10).…”
Section: Epidemiologic Levelmentioning
confidence: 99%
“…Large studies have found a link between the severity and/or control of both diseases in children and adults; in particular, poor asthma control is linked to moderate-severe rhinitis, which should be identified and treated (5). Numerous studies have also shown that treatment of AR will improve asthma outcome (1,5). According to some studies (8), asthma is more common in patients with moderate-to-severe persistent rhinitis; according to others, there is no correlation between ARIA categories of rhinitis and prevalence of asthma (9).…”
Section: Epidemiologic Levelmentioning
confidence: 99%
“…The respiratory apparatus is anatomically divided into the upper and lower respiratory tracts and has the function of air conduction and gas exchange [6]. Although considered as different entities, the nose and the lung share several microscopic and macroscopic similarities [6].…”
Section: Anatomical Evidencementioning
confidence: 99%
“…Although considered as different entities, the nose and the lung share several microscopic and macroscopic similarities [6]. Histologically, both nose and bronchi are composed of pseudostratified respiratory epithelium with columnar ciliated cells.…”
Section: Anatomical Evidencementioning
confidence: 99%
See 1 more Smart Citation